Enhancing Employee Performance: The Role Of Accounting Information Systems and Internal Control at the Deli Serdang Regency Inspectorate Office - Fahra Maisya Putri; Frenky Situmorang (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2024)
This study aims to determine the effect of accounting information systems and internal control on employee performance at the Deli Serdang District Inspectorate office. This study uses quantitative methods and the data source is primary data. The sample in this study were permanent employees who worked at the Inspectorate of Deli Serdang Regency totaling 77 respondents using saturated sample data collection techniques. Data analysis and testing consist of a validity test, reliability test, descriptive statistics, classical assumption test, multiple linear regression analysis, partial (T-test) and simultaneous (F test) hypothesis testing, and determination coefficient test. The results of this study indicate that the application of accounting information systems partially has a significant effect on employee performance with a value of T count (2.692) > T table (1.984). Internal control partially affects and is substantial to employee performance with a value of T count (2.116) > T table (1.984). The application of accounting information systems and internal control simultaneously has a significant effect on employee performance with a value of F count (6,992) > F table (3.12) and a coefficient of determination of (14.2%).